Strategi Produksi Film Dokumenter “Before You Eat” sebagai Kampanye Penghentian Isu Perbudakan Modern - Langi, Brian; Kusumawati, Dyah (UNIVERSITAS KALBIS, 2025)
The issue of slavery is a problem faced by a number of countries, not only in the enslavement of crew members but until now there is modern slavery, namely human trafficking. The study aims to determine the production strategy of the documentary film